2016
DOI: 10.1038/bmt.2015.339
|View full text |Cite
|
Sign up to set email alerts
|

Durable responses to ibrutinib in patients with relapsed CLL after allogeneic stem cell transplantation

Abstract: Ibrutinib, a recently approved inhibitor of Bruton's tyrosine kinase (BTK), has shown great efficacy in patients with high-risk CLL. Nevertheless, there are few data regarding its use in patients who relapsed after allogeneic stem cell transplantation (alloSCT). We report clinical data from five CLL patients treated with ibrutinib for relapse after first or even second allogeneic transplantation. Additionally, we performed analyses on cytokine levels and direct measuring of CD4 Th1 and CD4 Th2 cells to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
1
17
0
1
Order By: Relevance
“…One patient achieved MRD negativity. 13 Ibrutinib was tolerated with a safety profile similar to the one observed in the overall population of patients with R/R CLL treated with ibrutinib in the phase 3 clinical trial as part of the RESONATE study. In that cohort, 57% of patients in the ibrutinib group had at least 1 AE of grade 3 or higher.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One patient achieved MRD negativity. 13 Ibrutinib was tolerated with a safety profile similar to the one observed in the overall population of patients with R/R CLL treated with ibrutinib in the phase 3 clinical trial as part of the RESONATE study. In that cohort, 57% of patients in the ibrutinib group had at least 1 AE of grade 3 or higher.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported an observed decrease in serum Th2-type cytokines, including IL-10, IL-4, and IL-13, 12 and another similarly showed a decrease in IL-10 levels following treatment. 13 Here, we report for the first time comprehensive immune phenotype of B and T cells using primary samples from patients with CLL treated with ibrutinib following allo-HCT. Our results show that ibrutinib leads to dramatic depletion of Th2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 In this issue of Bone Marrow Transplantation, Link et al 9 provide further evidence of the beneficial role of ibrutinib in this context. In this study, five patients with extensively pre-treated high-risk CLL received ibrutinib for progressive CLL at a median of 28 months after alloHCT.…”
mentioning
confidence: 99%
“…16 In contrast, response rates of 88-100% have been observed in small series of patients who were treated with ibrutinib for CLL relapse after HSCT, resulting in prolonged disease control in the majority of them (with the option of reinstituting effective immunotherapy). 8,17,18 Not to say that it is not unlikely STI will increase the proportion of patients with refractory CLL that can be successfully bridged to transplant, thereby improving the overall outcome. This however means that also the ITT transplant results obtained in the HOVON trial might be not applicable to the current treatment landscape.…”
mentioning
confidence: 99%